EMPOWERING LEARNERS FOR JOB INTERVIEW: MEASURING THE EFFECTIVENESS OF AN AUTONOMOUS SPEAKING TEXTBOOK - Hendro Saptopramono,; Difiani Apriyanti,; Novi Fitria,; Witri Handayani,; Yaningsih, Yaningsih; Kotrini, Kotrini; Sabriandi Erdian,; Rina Anggraini, (International Journal of Social Science, 2025)
This study aims to assess the effectiveness of the autonomous speaking textbook, which provides detailed guidance for preparing to master English job interviews. This textbook provides detailed guidance on applying autonomous learning in speaking practice within a job interview context, along with rubrics and a weekly journal for autonomous purposes. The Design-Based Research (DBR) methodology was employed in this study, as it is more suitable for developing and evaluating educative innovations in authentic settings. The data were collected from the pre-test and post-test of the students' interviews, as well as survey results, to assess the students’ perceptions and strengthen the measurement of the effectiveness of 27 final-semester D4 English Department students at Politeknik Negeri Padang. The study's results reveal a significant improvement in the students’ speaking competence, particularly in terms of fluency, clarity, confidence, and vocabulary use. Most students felt that practicing mock interviews, receiving peer feedback, and keeping self-assessment journals helped them identify their strengths and weaknesses. These findings highlight the potential of an autonomous speaking textbook to bridge the gap between academic speaking activities and real-world job interview demand. Thus, it offers practical implications for EFL pedagogy and the development of employability skills